PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA - I Dewa Gede Kurnia Yudhana Dwi Anggara; Renny Husniati (ITB AAS INDONESIA, 2022)
This research is a quantitative research with the aim of analyzing the effect of work motivation, work discipline, and work environment on employee performance at the Tangerang City Personnel and Human Resources Development Agency. BKPSDM is an agency that has the task of handling the field of staffing and development of Civil Servants. In this study, the population was BKPSDM employees with non-echelon/staff/executive positions, which was determined by the number of samples as many as 80 respondents using purposive sampling method and data were collected by distributing questionnaires via google form. In this study using descriptive analysis techniques and inferential analysis using SmartPLS 3.2.9. In this study, the results obtained R Square value of 0.721 or 72.1%, then the results of hypothesis testing in this study are as follows, (1) there is a positive and significant influence between work motivation on employee performance which has an influence of 0.469, (2) there is a positive and significant influence between work discipline on employee performance which has an influence of 0.278, and (3) there is a positive and significant effect between the work environment on employee performance which has an influence of 0.240.